Heavy metals (Cd, Cu, Ph and Zn) concentrations in telescopium telescopium from Dumai Coastal Waters, Indonesia - Amin, Bintal; Ismail, Ahmad; Mohd Salleh, Kamarudin; Arshad, Aziz (Universiti Putra Malaysia Press, 2005)
Concentrations of cadmium, copper, lead and zinc in the marine gastropod, Telescopium telescopium, were determined to provide background information on heavy metal levels in the Straits of Malacca in the Indonesian side. Samples ofT. telescopium were collected from intertidal Dumai coastal waters at four stations inJuly 2004. The results of the present study showed that metal concentrations in the soft tissue ofT. telescopium varied at different sampling stations: 0.33 - 0.69 )1g/g; 9.38 - 52.29 )1g/g; 1.73 - 10. 78 )1g/g; 14.69 - 69.87 )1g/g dry weight far cadmium, copper, lead and zinc, respectively. Samples from Sungai Dumai station accumulated mare heavy metals when compared to other stations. Smaller T. telescopium accumulate mare metals than larger ones. Negative carrelations between metal concentrations and size (length and weight) were obseroed (except Cd and Cu in samples from Sungai Mesjid) with some variation in the carrelation coefficients which indicated metal regulation lJy the T. telescopiurn. Sungai Dumai showed the highest Metal Pollution Index (MPl) of 12.57 and Tomlinson Pollution Load Index (PLI) of 34.35 with Lubuk Gaung showing the lowest with 3.26 and 8.89, respectively. In general, the MPI and PU values indicate that metal pollution in Dumai coastal waters is not a serious threat yet and no drastic rectification measures are needed. However, as one of the most developing regions in Sumatera, further studies are necessary to assess temparal variation in metal accumulation and concentration for this species and other possible indicator organisms as well as in sediment from the surrounding areas in order to gain a better understanding of pollution status in Dumai coastal waters.